Bioavailability and bioaccessibility of arsenic in a soil amended with drinking-water treatment residuals - Nagar, Rachana; Sarkar, Dibyendu; Makris, Konstantinos C.; Datta, Rupali K.; Sylvia, Victor L. (My University, 2009)
Earlier incubation and greenhouse studies in our laboratory confirmed the effectiveness of drinking-water treatment residual (WTR) in decreasing soil arsenic (As) bioaccessibility as determined with in vitro tests, which led us to hypothesize a similar outcome if animal studies were to be conducted. Our objective was to evaluate the potential of WTR in lowering soil As bioavailability by conducting in vivo experiments and compare the in vitro to the in vivo As data. This study was performed using 6-week-old male BALB/c mice that were fed with an As-contaminated soil slurry using the gavage method. Blood and stomach contents were collected at 1 and 24 h after feeding. Urine and excreta were collected at time 0 (before feeding) and 24 h after feeding. Relative As bioavailability (RBA) values calculated from the blood samples of mice fed with WTR and WTR-amended soil samples ranged from 13% to 24% and from 25% to 29%, respectively; both were significantly (p < 0.001) lower than that of the unamended (no-WTR) soil (~100% RBA). Absolute As bioavailability (ABA) in the gastric phase was significantly (p < 0.001) lowered, to 7-16%, in the WTR-amended soil compared with that of the unamended control (26%). A significant (p < 0.001) linear correlation (r = 0.94) was observed between the in vitro (stomach-phase) and the in vivo RBA data. Percentage recovery of As obtained from four mice tissue compartments (i.e., blood, stomach, urine, and fecal matter) after oral and intramuscular administrations was 63-80%. Results illustrate the effectiveness of in situ WTR amendment in decreasing in vivo soil As bioavailability, thereby lowering the potential cancer risk via an oral ingestion pathway.
Keywords: Aluminum; Arsenic; Iron; Water treatment; Greenhouse ecosystem; Drinking water; Bioavailability